A Comparative Study of Phase States of the Peribacteroid Membrane from Yellow Lupin and Broad Bean Nodules - Natalia N. Kudryavtseva; Alexis V. Sof’in; Georgiy S. Bobylev; Evgeny M. Sorokin (Biochemistry Research International)
A comparative study of the lipid bilayer phase status and structure of the outer membrane of free-living Bradyrhizobium strain 359a (Nod+Fix+) and 400 (Nod+FixL) or Rhizobium leguminosarum 97 (Nod+Fix+, effective) and 87 (Nod+FixL, ineffective) has been carried out. Also, the effect of the symbiotic pair combination on the lipid bilayer structure of the bacteroid outer membrane and peribacteroid membrane, isolated from the nodules of Lupinus luteus L. or Vicia faba L., has been studied. As a result, it is shown that the lipid bilayer status of the bacteroid outer membrane is mainly determined by microsymbiont, but not the host plant. In the contrast, the lipid bilayer status of the peribacteroid membrane and, as a consequence, its properties depend on interaction of both symbiotic partners.